Intellectual traditions in Islam - Daftary, Farhad (London ; New York : I.B. Tauris in association with The Institute of Ismaili Studies ; New York : in the United States of America and Canada distributed by St. Martins Press, 2000)
Includes bibliographical references (p. 225-238) and index.